2021
DOI: 10.3389/fnmol.2020.613421
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Chronic High-Dose Corticosterone-Induced Aggravation of Cognitive Impairment in APP/PS1 Transgenic Mice

Abstract: Clinical studies have found that some Alzheimer’s disease (AD) patients suffer from Cushing’s syndrome (CS). CS is caused by the long-term release of excess glucocorticoids (GCs) from the adrenal gland, which in turn, impair brain function and induce dementia. Thus, we investigated the mechanism of the effect of corticosterone (CORT) on the development and progression of AD in a preclinical model. Specifically, the plasma CORT levels of 9-month-old APP/PS1 Tg mice were abnormally increased, suggesting an assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…multi-level anti-inflammatory effect, are not proper drugs to ameliorate neuroinflammation. It is proven that chronically elevated plasma GCs levels promote AD pathomechanisms, accelerate cognitive dysfunction and are referred to as a risk factor for AD and PD [ 96 , 97 ]. Taking this into account, we hypothesize that in the research field CGs may be useful as agents exacerbating course of neuroinflammation and can contribute to modeling the severe course of neurodegeneration.…”
Section: Therapeutic Strategies Targeting Neuroinflammation and Cogni...mentioning
confidence: 99%
“…multi-level anti-inflammatory effect, are not proper drugs to ameliorate neuroinflammation. It is proven that chronically elevated plasma GCs levels promote AD pathomechanisms, accelerate cognitive dysfunction and are referred to as a risk factor for AD and PD [ 96 , 97 ]. Taking this into account, we hypothesize that in the research field CGs may be useful as agents exacerbating course of neuroinflammation and can contribute to modeling the severe course of neurodegeneration.…”
Section: Therapeutic Strategies Targeting Neuroinflammation and Cogni...mentioning
confidence: 99%
“…Furthermore, epidemiologic clinical studies suggest the use of the analysis of long-term cortisol measurements as a biomarker to help the diagnosis of people with AD ( Ennis et al, 2017 ). A previous study showed that 9-month-old APP/PS1 transgenic mice exhibit high plasma corticosterone levels ( Zhang S. Q. et al, 2021 ). Moreover, chronic administration of corticosterone accelerates cognitive impairment and increases Aβ plaque formation in the hippocampus and prefrontal cortex of these animals ( Zhang S. Q. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this pathological aging phenotype, we report a chronic state of stress in male hAPP23+/− mice, represented by chronically elevated circulating corticosterone levels, associated with lower body weights and survival rates. Elevated corticosterone levels have previously been measured in APP/PS1 transgenic mice [29] but were not followed up in time. Moreover, decreased body weights were previously observed in the same hAPP23+/− breeding line at our institute [35], as well as in other AD mouse models such as the Tg2576, APP/PS1, and TgCRND8 transgenic mice [36,37] and AD patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, stress is known to activate the hypothalamic-pituitary-adrenal (HPA) axis, leading to rapid synthesis and release of glucocorticoids (cortisol in humans and corticosterone in rodents) into the bloodstream. Hypercortisolism has been reported as a risk factor for AD [29,[39][40][41][42] because it encompasses decreased brain structure volumes [26,43,44], impaired neuronal function, and drives neurons to cell death [45]. Accordingly, subclinical Cushing syndrome, characterized by elevated cortisol levels, has been reported as a potential cause of metabolic dementia and rapidly progressive Alzheimer-type dementia [25,27,28,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation